Morbidity and mortality weekly report, Vol. 21, no. 14, For week ending April 8, 1972 - Center for Disease Control; United States Dept. of Health, Education, and Welfare Public Health Service; United States Health Services and Mental Health Administration
Table 1. Cases of specified notifiable diseases: United States -- Table 2. Notifiable diseases of low frequency -- Table 3. Cases of specified notifiable diseases: United States for weeks ended April 8,1972 and April 10, 1971 (14th week) -- Table 4. Deaths in 122 United States cities for week ended April 8, 1972 Epidemiologic notes and reports: Human rabies - Texas -- Gastroenteritis - New York -- Measles - Los Angeles County, California -- Carbon monoxide poisoning - South Dakota -- Gastroenteritis - Alaska Surveillance summary: Animal rabies - United States, January 1972 -- Legal abortions - United States, January - March 1971 International notes: Follow-up on smallpox - Yugoslavia Table 1. Food specific attack rates among restaurant patrons with gastroenteritis - New York, November 1971 -- Table 2. Reports of rabies in animals, by type and state, United States - January 1972 -- Table 3. Reported legal abortion ratios by state of occurrence selected states - January - March 1971 -- Table 4. Reported legal abortions by type of procedure and state of occurrence, selected states - January - March 1971 -- Table 5. Reported leagal abortions, by age and state of occurrence, selected states - January - March 1971 Figure 1. Yugoslavia -- Figure 2. Gastroenteritis cases among restaurant patrons, Upstate New York - November 11-20, 1971 -- Figure 3. Gastroenteritis cases among village residents and restaurant employees, Upstate New York - September 30 - November 21, 1971 -- Figure 4. Measles cases, by week of report, Los Angeles County, California - 1971-1972 -- Figure 5. Gastroenteritis cases by date of onset, Alaska highway - August 20 - September 2, 1971 -- Figure 6. Travel routes between Fairbanks, Alaska and Whitehorse, Yukon Territory, Canada